The Problem of Perception of the Concept «Constitutionalism» in the Republic of Artsak - Harutyunyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2018)
The article presents the problem of the perception of constitutionalism in the Republic of Artsakh, which has not been de jure recognized by the international community yet, but has all the attributes of the state. In the end, it is substantiated that the establishment of constitutionalism in the country will be an additional incentive both to enhance the country's reputation and, in the future, for international recognition.
Keywords: Republic of Artsakh, Constitution, constitutional axiology